SISTEM PELAYANAN REKAM MEDIS PASIEN RAWAT JALAN DI UPTD PUSKESMAS KARANGREJA KABUPATEN PURBALINGGA - Ajeng Renita Handayani; Taufik Purboyo Purboyo; Farida Nur Aini (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
Various problems related to medical record services at UPTD Karangreja Community Health Center, Purbalingga Regency, such as non-compliance with procedures and lack of compliance with service guidelines, became the background for researching the Outpatient Medical Record Service System at Uptd Karangreja Community Health Center, Purbalingga Regency. This research uses a descriptive qualitative method with an interactive analysis model as the data analysis method. The research results show that medical record services are sufficient in accordance with applicable standard operational procedures. However, there are still several aspects that are not appropriate, such as in the aspect of returning medical records, there are some that do not comply with the regulations regarding the time period for medical records to be returned to the medical records room. During the registration and medical record management process, there are also cases where patient data is incomplete because the patient does not bring the required identification. Then some of the medical record sheets for nurses and doctors are incomplete. This is due to a lack of service time so that a lot of information that should be filled in by nurses and doctors is only filled in with the important and more prioritized parts. Several improvements can be made, including by disseminating SOPs for medical records so that delays in returning medical records and filling in incomplete medical records can be avoided. Apart from that, officers are sent to take special training on medical records so that the skills of medical record personnel can help the administration of medical records run better.